Pengaruh Pelatihan Dan Motivasi Kerja Terhadap Kinerja Mengajar Guru Ipa Di Smp Se-Kota Poso - Indri Novayanti Gala; H. Achmad Ramadhan; Amram Rede (Universitas Tadulako, 2017)
The purpose of this research was to analyze the influence of training and work motivation of Science Teachers Teaching Performance in Junior High School in Poso. This research is quantitative descriptive survey method conducted from October to December 2015. Population and samples are 33 respondents. Instruments used as a data collectionis a questionnaire with multiple regression analysis techniques. Hypothesis test results obtained Fcount > Ftable (4,978 > 3,316) and contributions influence of 24,9%. Thus, the results of this study povide information that the training and work motivation to have influence of Science Teachers Teaching Performance in Junior High School in Poso.